Utilization of ICT for industrial promotion on a japanese remote island - Hiroaki Kammura (Netcom)
Remote islands in Japan face decline of population. In response, various policies have been implemented to promote their revitalization. In recent years, the deployment of broadband across Japan has led to expectations for its utilization on remote islands. This paper discusses the influence of improvements in the information and communication environment on industrial activities on remote islands.